Analyses of MADS-box Genes Suggest HvMADS56 to Regulate Lateral Spikelet Development in Barley - Mohammed A. Sayed; Mohamed Allam; Quinn Kalby Heck; Ieva Urbanavičiūtė; Twan Rutten; David Stuart; Shakhira Zakhrabekova; Andreas Börner; Klaus Pillen; Mats Hansson; Helmy M. Youssef (Plants, 2021)
MADS-box transcription factors are crucial regulators of inflorescence and flower development in plants. Therefore, the recent interest in this family has received much attention in plant breeding programs due to their impact on plant development and inflorescence architecture. The aim of this study was to investigate the role of HvMADS-box genes in lateral spikelet development in barley (Hordeum vulgare L.). A set of 30 spike-contrasting barley lines were phenotypically and genotypically investigated under controlled conditions. We detected clear variations in the spike and spikelet development during the developmental stages among the tested lines. The lateral florets in the deficiens and semi-deficiens lines were more reduced than in two-rowed cultivars except cv. Kristina. Interestingly, cv. Kristina, int-h.43 and int-i.39 exhibited the same behavior as def.5, def.6, semi-def.1, semi-def.8 regarding development and showed reduced lateral florets size. In HOR1555, HOR7191 and HOR7041, the lateral florets continued their development, eventually setting seeds. In contrast, lateral florets in two-rowed barley stopped differentiating after the awn primordia stage giving rise to lateral floret sterility. At harvest, the lines tested showed large variation for all central and lateral spikelet-related traits. Phylogenetic analysis showed that more than half of the 108 MADS-box genes identified are highly conserved and are expressed in different barley tissues. Re-sequence analysis of a subset of these genes showed clear polymorphism in either SNPs or in/del. Variation in HvMADS56 correlated with altered lateral spikelet morphology. This suggests that HvMADS56 plays an important role in lateral spikelet development in barley.